The Impact of Switching Costs on the Outsourcing of Knowledge‐Intensive Business Processes1. (8th January 2016) - Cui, Zhijian
ABSTRACT: This study examines the impact of switching costs on vendor selection and contract efficiency in the outsourcing of knowledge‐intensive business services (KIBS). We show that under most plausible scenarios in KIBS outsourcing, there is an intrinsic tension between vendor selection and contract efficiency: in the process in which the winning vendor's bid constitutes the terms of the contract between client and vendor (e.g., competitive bidding), there is good selection but contract inefficiency (positive information rent paid by the client). If, by contrast, the client establishes the contract terms, then its performance yields contract efficiency but poor selection. We also highlight the implications of performance metrics for contract design in KIBS outsourcing.